Forêts et sociétés en Languedoc (Néolithique final' Antiquité tardive) L'anthracologie, méthode et paléoécologie - Chabal, Lucie (Documents d'archéologie française, 1997)
Besides identifying plants used by men, charcoal analysis may also reconstruct the history of forests, based on the study of charcoal from domestic uses. The reliability of this discipline depends on the definition of rigourous methods, from the archaeological dig to the palaeoenvironmental interpretation, which is the subject of the tint part of this work.In part two, thirteen languedocian sites dating from the end of Prehistory to Antiquity are studied following this method. In the Languedoc region, the early balance between the mediterranean oak forest and human activities leads us to review the history of deforestation. It is only in the lion Age that permanent tree clearance on plains increases, maintained during the roman period, announcing perhaps the first permanent fields. The results of this study, combined with documentary sources, constitute a first synthesis on territory changes.